1988 grain dust explosions lowest since 1975 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Twelve grain dust explosions were reported in the U.S. in 1988 according to data compiled by Ralph Regan, FGIS Safety Director and Robert W. Schoeff, Extension Marketing and Safety Specialist, Kansas State University. This compares to 15 in 1987 and a 10 year average of 20 explosions.
Keywords: Grain dust; Dust explosions